Linguistik Lanskap di Museum Lontar Gedong Kirtya - Suari, Anak Agung Putu (International Seminar on Austronesian Languages and Literature, 2021)
Landscape Linguistics (LL) is about how language is represented in public spaces. This study describes the use of language to explain historical objects in the Museum Gedong Kirtya using the LL study. This qualitative research describes the variant language and its function to give information in the Museum Gedong Kirtya. The objects of this study are photos of museum signs and objects labels or exhibit labels. Twenty photos are taken and used for analysis. The photos are classified based on two groups: museum signs and exhibit labels. Twenty photographs were taken and used for analysis. The photos are classified according to two groups: museum signs and exhibit labels. The results shows that the languages ??used were monolingual, bilingual, and multilingual—Balinese, Indonesian, English, and Dutch. Indonesian and English are dominantly used as museum signs and exhibit labels in describing museum historical objects, especially related to the process of making lontar manuscripts. In addition, both languages ??are used to indicate museum signs, for example, the prohibition sign and the welcome sign. The Balinese language is used in the form of Balinese script and as a cultural tradition. Dutch is used for information. The construction of the Gedong Kirtya museum was established during the Dutch government